The comparative analysis of eu and turkish laws in the aspect of mergers & acquisitions - Peker, Hayriye Elçin (My University, 2007)
unknown
Keywords: Avrupa Birliği Hukuku; Rekabet_Şirketler; Şirketlerin Birleşme ve Bütünleşmeleri